2013
DOI: 10.1371/journal.pone.0060212
|View full text |Cite
|
Sign up to set email alerts
|

Association of TCF7L2 Gene Polymorphisms with T2DM in the Population of Hyderabad, India

Abstract: We attempt to evaluate the nature of association of TCF7L2 gene variants with T2DM, for the first time in the population of Hyderabad, which is considered to be diabetic capital of India. It is a case-control study of the three SNPs of TCF7L2, rs7903146, rs12255372 and rs11196205, genotyped on Sequenom Massarray platform, in a sample of 758 patients and 621 controls. The risk allele frequency of the three SNPs was found to be significantly higher in the T2DM cases than controls, implicating susceptibility for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 50 publications
1
35
2
Order By: Relevance
“…Furthermore, a number of meta-analyses supported this robust finding [30,31]. The replication studies of TCF7L2 gene variants among Indian populations also showed a strong association of TCF7L2 with T2DM [32][33][34][35][36]. Investigations on transcriptional regulation by applying chromatin immunoprecipitation and sequencing techniques in a colorectal cancer cell line revealed overexpression of TCF7L2.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, a number of meta-analyses supported this robust finding [30,31]. The replication studies of TCF7L2 gene variants among Indian populations also showed a strong association of TCF7L2 with T2DM [32][33][34][35][36]. Investigations on transcriptional regulation by applying chromatin immunoprecipitation and sequencing techniques in a colorectal cancer cell line revealed overexpression of TCF7L2.…”
Section: Discussionmentioning
confidence: 77%
“…TCF7L2 gene is considered one of the most important candidate genes for T2DM, playing a key role in blood-glucose homeostasis and beta-cell function (30). Following the initial report by Grant and cols.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, none of the variants found in TCF7L2 exons were associated with T2DM (30). Thus, it is necessary to clarify how the intronic variants affect TCF7L2 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Despite increasing evidence that the TCF7L2 gene is associated with an increased T2DM risk in ethnic groups worldwide (Hayashi et al, 2007;Miyake et al, 2008;Palizban et al, 2012;Uma Jyothi et al, 2013;Wang et al, 2013), some studies presented the opposite conclusion (Chang et al, 2007;Ng et al, 2007;Zheng et al, 2012a). No consistent results have been reported because of the limited sample size and ethnicity heterogeneity in the studies.…”
Section: Discussionmentioning
confidence: 94%